Polityka językowa i tożsamość etniczna w Tatarstanie - Usmanov, Marat (Studia Azjatystyczne, 2015)
Tatarstan is a multinational republic in the Russian Federation with complex linguistic and ethnic relations, being at the same time strategically and economically important for the state. Despite the complexity and the threat of potential conflict in the social and political reality in Tatarstan, the region shows an ability to manage ethnic diversities effectively. Tatarstan maintains a balance of interests of different ethnic groups and uses its multinational character as a positive resource, unlike other multiethnic regions of Russia, where recently there have been conflicts between various ethnic groups. This article is devoted to the analysis of language policy in Tatarstan and adaptation strategies for multiethnic population of the state. The ethnic composition of the population of the region determines its complex linguistic situation and makes language policy difficult to implement. One of the most urgent problems of language policy in Tatarstan is the need to consider the interests of languages of different ethnic communities. Each languagehas its own problem areas and needs various support measures. The linguistic situation in Tatarstan is determined primarily by the position of the Tatar and Russian languages as spoken by the most numerous ethnic groups. The article discusses the ways of the common use of Tatar and Russian in various spheres of public life in the region.